Security culture on the Internet based on the opinions of primary school students - Mavrić Mina; Bećirović-Alić Maida; Smailović Semrija (Univerzitetska Misao)
The research problem is aimed at looking at the opinions of elementary school students about knowing the dangers that exist on the Internet.. The socio-demographic structure of the sample, as a predictor model of the research, enabled the perception of the influence of certain variables on students' attitudes about dangers on the Internet. These are: gender, class, living environment (village-city), family structure, work and educational status of both parents. The research was conducted in order to determine whether students' attitudes regarding the recognition of dangers on the Internet differ statistically significantly with respect to the control variables of the research. The research included primary school students. The results of the research indicate that the structure and educational status of the family as important control variables directly affect the nature of students' attitudes about dangers on the Internet. A statistically significant difference in attitudes was established with regard to age, but in relation to gender and the work status of parents, there is no statistically significant difference in the attitudes of students about the dangers of the Internet.